2022
DOI: 10.1051/0004-6361/202142450
|View full text |Cite
|
Sign up to set email alerts
|

Cyanopolyyne line survey towards high-mass star-forming regions with TMRT

Abstract: Context. Cyanopolyynes (HC2n+1 N, n = 1,2,3), which are the linear carbon chain molecules, are precursors for the prebiotic synthesis of simple amino acids. They are important for understanding prebiotic chemistry and may be good tracers of the star formation sequence. Aims. We aim to search for cyanopolyynes in high-mass star-forming regions (HMSFRs) at possibly different evolutionary stages, investigate the evolution of HC3N and its relation with shock tracers, and detect the existence of HC5N and HC7N in HM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 123 publications
0
1
0
Order By: Relevance
“…where k and W are the Boltzmann constant and the integrated line intensity, respectively, Q(T rot ) = 4.58 T rot + 0.28 is the partition function for HC 3 N (Wang et al 2022), T rot and N are the rotational temperature and the column density, respectively, and the Sµ 2 , ν and E u values are taken from the CDMS catalog (see Section 2.2).…”
Section: Line Widthmentioning
confidence: 99%
“…where k and W are the Boltzmann constant and the integrated line intensity, respectively, Q(T rot ) = 4.58 T rot + 0.28 is the partition function for HC 3 N (Wang et al 2022), T rot and N are the rotational temperature and the column density, respectively, and the Sµ 2 , ν and E u values are taken from the CDMS catalog (see Section 2.2).…”
Section: Line Widthmentioning
confidence: 99%
“…He et al (2021) andWang et al (2022).4.4.2. Outflow Orientations Indicated by H 2 O Maser and SiO J = 5-4 Emissions H 2 O, SiO masers, and SiO nonmasing emissions have been employed in previous studies to investigate outflows, as demonstrated by…”
mentioning
confidence: 99%